2021
DOI: 10.3390/curroncol28060360
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Diagnosis and Treatment of Lung Cancer at a Canadian Academic Center: A Retrospective Chart Review

Abstract: The large burden of COVID-19 on health care systems worldwide has raised concerns among medical oncologists about the impact of COVID-19 on the diagnosis and treatment of lung cancer patients. In this retrospective cohort study, we investigated the impact of COVID-19 on lung cancer diagnosis and treatment before and during the COVID-19 era. New lung cancer diagnoses decreased by 34.7% during the pandemic with slightly more advanced stages of disease, there was a significant increase in the utilization of radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 23 publications
5
39
1
1
Order By: Relevance
“… 8 A slight reduction in newly diagnosed lung cancer cases was observed in 2020 compared to 2019 in several other studies. 28 , 29 , 30 , 31 However, some studies have observed relevant decrease in lung cancer diagnoses 32 , 33 likely due to the disruption of lung cancer screening 34 , 35 , 36 or to the different setting of the study (hospital vs population‐based). Lung cancer screening is not available in Italy.…”
Section: Discussionmentioning
confidence: 99%
“… 8 A slight reduction in newly diagnosed lung cancer cases was observed in 2020 compared to 2019 in several other studies. 28 , 29 , 30 , 31 However, some studies have observed relevant decrease in lung cancer diagnoses 32 , 33 likely due to the disruption of lung cancer screening 34 , 35 , 36 or to the different setting of the study (hospital vs population‐based). Lung cancer screening is not available in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…As approximately 25% of advanced NSCLC have high PD-L1 expression, these findings suggest a general reduction in pathologic diagnoses of all lung cancers. A retrospective study in Quebec, Canada, observed a 34.7% decrease in all lung cancer diagnosed at a single institution between March 2020 and February 2021 (Kasymjanova et al 2021 ). Similarly, in a bicenter retrospective study from Spain, new NSCLC and small cell lung cancer diagnoses were 38% lower between January and June 2020 than a baseline period of January to June 2019 (Reyes et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, access to health care services has been significantly limited as almost all healthcare workers are employed in the management of COVID-19 patients. Delays were also observed in cancer patients starting anticancer therapy or under follow-up [ 96 , 97 , 98 ]. Notably, patients who experienced either an interruption or failure to start therapy because of COVID-19 had a statistically shorter overall survival than those who remained on treatment [ 97 ].…”
Section: The Impact Of Covid-19 On Cancer Patientsmentioning
confidence: 99%